Variable Voltage Source Inverter with controlled frequency spectrum based on Random Pulse Width Modulation - Muhammad Farrukh Yaqub; Muhammad Safian Adeel; Tahir Izhar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
This paper presents a new method for single phase variable voltage inverter based on Random Pulse Width Modulation. In Random Pulse Width Modulation based inverter, the frequency spectrum of the output current and voltage waveforms becomes continuous because of the randomization of the switching function of the devices controlling the output voltages. This paper establishes a theory that if the distributions of the random numbers generated by the random source are kept within certain limit with respect to the peak value of reference sinusoidal waveform, the frequency spectrum can be controlled. On the basis of the results, a novel drive using variable tap changing transformer (optional) and adaptive random number generator, to control the ratio between the numbers generated by the random source and the reference waveform has been suggested that will guarantee a better power quality profile for a broad range of output voltages.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.150